2011
DOI: 10.1532/hsf98.20101173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neurocognitive Functions after Beating-Heart Mitral Valve Replacement without Aorta Cross-Clamping and after Standard Mitral Valve Replacement with Cardioplegic Arrest

Abstract: The technique of mitral valve replacement with normothermic CPB without cross-clamping of the aorta may be safely used for the majority of patients requiring mitral valve replacement without causing deterioration in neurocognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Our team is accustomed to performing beating heart cardiac surgery in dogs and large animal species (e.g., sheep, pigs, cattle) . We believe that keeping the heart beating during CPB (as performed in the present case), compared to cardiac arrest, diminishes the risks of ischemia–reperfusion injury that has been observed in people for mitral surgery . Cardiopulmonary bypass can alter normal hemostatic balance and predispose patients to the risk of excessive postoperative bleeding .…”
Section: Discussionmentioning
confidence: 83%
“…Our team is accustomed to performing beating heart cardiac surgery in dogs and large animal species (e.g., sheep, pigs, cattle) . We believe that keeping the heart beating during CPB (as performed in the present case), compared to cardiac arrest, diminishes the risks of ischemia–reperfusion injury that has been observed in people for mitral surgery . Cardiopulmonary bypass can alter normal hemostatic balance and predispose patients to the risk of excessive postoperative bleeding .…”
Section: Discussionmentioning
confidence: 83%
“…The procedure could be the procedure of choice for the valve operation or combined operation (valve operation and CABG) in high-risk patients with low ejection fractions 9 . Kervan et al concludes that the technique of mitral valve replacement with normothermic CPB without cross-clamping of the aorta may be safely used for the majority of patients requiring mitral valve replacement without causing deterioration in neurocognitive function 10 . The advantages of on-pump beating mitral valve replacement are due to the fact that the heart is under more physiologic conditions than cardioplegic arrested state with left ventricular beating tonus, thus eliminating adverse effects of global myocardial ischemia produced from reperfusion injury.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Hyperventilation caused by increased anger levels has also been shown to result in vasospasms and arrhythmia, even in healthy individuals. [8,9] In addition, some studies have reported that anger may lead to a ventricular ectopic beat and tachycardia, which can lead to myocardial infarction. [10][11][12] A change in cerebral activity during emotional stress can also lead to the presence of nonhomogenous repolarization fields as the electrical stability deteriorates.…”
Section: Discussionmentioning
confidence: 99%